P2 Difficulties in managing a patient with multi-organ damage in systemic lupus erythematosus and a high risk of thrombotic events in antiphospholipid syndrome (case report). (23rd March 2020) - Cheldieva, Fariza; Reshetnyak, Tatiana; Shumilova, Anastasiia; Seredavkina, Natalia; Cherkasova, Maria; Lisitsyna, Tatiana; Borisova, Anastasia; Lila, Alexander
Abstract : Background: Systemic lupus erythematosus (SLE) is a multisystem disease with many clinical manifestations. Late diagnosis, kidney damage, neuropsychiatric disorders, high risk of thrombotic events, resistance to therapy worsen the prognosis of the disease and increase mortality. Methods: Description of a clinical case of multiple organ damages in a patient with SLE and concomitant antiphospholipid syndrome (APS). Results: We describe a case report of organ damage in a patient with SLE and concomitant APS. The clinical and laboratory manifestations for the entire period of the disease are given below (table 1 ). Now the main manifestation of the disease in clinical finding are: active lupus nephritis of a kidney, relapse of venous thrombosis as a result of APS, thrombotic microangioencephalopathy, cognitive impairment and somatogenic astheno-depressive syndrome. Conclusions: This clinical case demonstrates a patient with SLE presented in clinical features thrombosis, lupus glomerulonephritis class IV, AI 8, CI 2, high immunological disorders and concomitant APS. The difficulty in treating the patient is the consistently high immunological activity of the disease, the resistance of the therapy cytostatic and glucocorticoids, the inefficiency and intolerance of a number of oral anticoagulants: dabigatran etexilate and rivaroxaban — relapses of thrombosis, warfarin — the inability to reach the target levels of the international normalized ratio (INR) due to recurrent nosebleeds.